Competency Based State Civil Apparatus Structuring in The Framework of Bureaucracy Reform - Rosyida, Luthfiyah; Hakim, Abdul; Saleh, Choirul (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2020)
The direction of bureaucratic reform currently rests on the application of professional state civil apparatus (ASN) management, one of which is through competency based ASN structuring. Appropriate ASN structuring based on competence (the right man in the right place) will bring a positive impact on organizational performance. However, the mismatch between employee competencies and position and placement is still a major problem for ASN. The policies related to existing employee structuring are less effective, so it is necessary to formulate a more adaptive ASN structuring policy that animates Law Number 5 of 2014 concerning ASN, and a competency based ASN structuring model is needed that is more comprehensive. This research was conducted at DLH East Java Province using qualitative methods through a descriptive approach. Data were obtained from observations, interviews and documentation studies which are then processed with an interactive data analysis model. The results showed that the implementation of ASN structuring in DLH East Java Province was still not optimal due to internal and external inhibiting factors. The recommended new model is a model that integrates instruments in structuring existing employees with new instruments such as competency testing and competency enhancement in accordance with the merit system and by involving the role of several stakeholders directly related to the implementation of the ASN structuring.